Redefining Digital Library Boundaries: Being More than an Information Silo - Bainbridge, David (Journal of Information and Knowledge, 2019)
This article is the final in a series of three publications that reflect on the boundaries and perceptions of what we think of when we hear the term Digital Libraries, with reference to our mainstream digital library systems. In this article we present three digital library examples that push the implementation envelope in terms of digital library systems functionality, thereby challenging expectations and assumptions about what our mainstream digital library systems are capable of delivering. The first example integrates a Digital Music Stand with a digital library environment, and in doing so extends the role of the digital library to include fine-grained interaction and access to document content. The second example is a digital library that supports musicological analysis, and shifts the boundaries of where and how the digital library operates. This second example is notable as it breaks out of the silo mindset prevalent in mainstream DLs software architecture designs. The trends of enhanced flexible and permissive capabilities continue through the third example, where we present a crowdsourced pop-trivia music video website with a Guitar Hero game challenge element. While this description might seem far removed from the notion of a digital library, it is in fact implemented using an off-the-shelf open source digital library solution, where all the additional functionality introduced is achieved through the inclusion of supplemental JavaScript and XSLT files—no change to the digital library architecture is needed. While the three chosen examples all happen to be musical in nature, this is really incidental to the main points being made, and the article concludes by generalising the discussion to other forms of digital library.